Analisis Pengukuran Kinerja Rantai Pasok Komoditas Tuna Menggunakan Metode Supply Chain Operation Reference Pada Perusahaan Eksportir Ikan Tuna Di Kota Bitung - Faizza, Fatimah Nur; Sholihah, Sita Aniisah; Firmansyah, Iqbal (Institut Transportasi dan Logistik Trisakti, 2025)
Tuna commodities play a crucial role as the second-largest fisheries export commodity, significantly contributing to Indonesia's foreign exchange. Indonesia holds substantial potential to dominate the international tuna market, with North Sulawesi emerging as the largest producer in 2021, reaching 56,205,302 kg. However, despite this, the export volume of North Sulawesi Province decreased by 6.6% in 2020-2021, indicating that the potential tuna supply has not been fully optimized. To maintain consistency and enhance the export supply chain performance of tuna products, transparency is required from upstream to downstream, involving planning, procurement, production, marketing, and distribution in the supply chain system. Efforts to improve the supply chain system involve evaluating performance through measurement. This research aims to measure the performance of the tuna commodity supply chain in North Sulawesi, applying the Supply Chain Operations Reference (SCOR) method and weighting each supply chain performance metric using the Analytical Hierarchy Process (AHP). Measurement results indicate that the performance of the tuna commodity supply chain in an exporting company in Bitung City, North Sulawesi, reaches a value of 69.421, categorizing it as